DAMPAK RESTRIKSI EKSPOR BAHAN BAKU SEMIKONDUKTOR JEPANG TERHADAP PEREKONOMIAN KOREA SELATAN - Dewi Harnum; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Cooperation is carried out by each country to meet the needs of its country and interact with other countries that have similar interests and are mutually dependent. Japan and South Korea are two countries with a high level of economy Ithe world. The country has trade relations in the semiconductor sector where Japan exports semiconductor raw materials to South Korea. On July 1, 2019 Japan imposed restrictions on some semiconductor raw materials to South Korea in retaliation for a series of South Korean court decisions. This qualitative research adopts the perspective of neoliberalism and it analyzed with the protectionism theory of Friedrich List for his role as an actor. This research uses the level of analysis of the Nation-State by Mohtar Mas’oed and the concept of national interest by Holsti. Secondary data comes from books, journals, news from the BBC, Britannica, articles, and websites. This study shows that Japan carried out a restriction policy because of a South Korean court decision that asked Japan to compensate South Korean victims of forced labor during World War II. These restrictions mean that whenever a Japanese company wants to export to South Korea, the licensing process is more complicated and can take up to 90 days. Keywords: Export Restriction, Semiconductor Trade, Nation-State, Level of Analysis